Eksplorasi Unsur-Unsur Mind-Body Therapy Dalam Tradisi Appassili Suku Makassar Pada 7 Bulanan Ibu Hamil - Rahma, Nur; Mardianthy, Nurul Rezky; Rasnita, Rasnita; Asfarada, Muhammad Rizky; Nurkhalifa, Nihar; Mulhaeriah, Mulhaeriah (Universitas Tribhuwana Tunggadewi, 2023)
The Appassili tradition is a customary ceremony of the Makassar tribe at the age of seven months of pregnancy that is believed to be a ritual of self-purification for the mother and fetus for protection from bad things until the end of the process of childbirth. The study aims to explore the elements of mind-body therapy in the Appassilian tradition. This research uses non-empirical qualitative ethnographic research methods. The study used snowball sampling techniques and obtained 17 informants, consisting of 15 pregnant women and two Sanro people (traditional birth attendants or people trusted to help with childbirth) as key informants. Data collection is carried out through in-depth interviews and field observations, with data analysis using OpenCode software. The results obtained five themes, namely: 1) physical and mental conditions during pregnancy; 2) abstinence during gestation; 3) forms of belief in the Appassili's; 4) the meaning of the procession of the Appassili's; and 5) benefits derived from the Appasili's. There are elements of mind-body therapy in the Appassili tradition, namely prayer, respiratory therapy, and autogenic relaxation. In addition, there is an element of manipulative and body-based therapy in the Appassili, which is the therapy that sanro performs on the stomachs of pregnant mothers. The advice for future researchers further explores how the role of health care can be combined with the culture that is inherent in society.